Patient Perspectives of Diabetes and Diabetic Retinopathy Services in Kiribati: A Qualitative Study. (September 2021) - 'Ofanoa, Malakai; Tekeraoi, Rabebe; Dalmia, Prarthana; Ram, Komal; Pal, Moneeta; Nosa, Vili; Goodyear-Smith, Felicity
Diabetes mellitus is an increasing global health problem affecting millions of people worldwide, especially true in the Republic of Kiribati, with >20% of adults suffering from type 2 diabetes, and the prevalence is rising. Information on I-Kiribati patients' understanding of diabetes and perception of access to relevant services is sparse. This study explores patient perspectives on their condition and its management using Talanga and Kakala Pacific research methodologies. Data were collected from Kiribati patients in four focus group interviews. Key themes to emerge were knowledge about diabetes, understanding and accessing the health care system, making lifestyle changes, and suggestions for improvement. Health system failures to meet the complex health care needs of these patients and health care services gaps are apparent. Improvements suggested include a comprehensive village-based health promotion and community development program focusing on youth and schools from early childhood and onward, increase in the skilled workforce, and an integrated approach to service delivery.